2020
DOI: 10.1097/gox.0000000000002529
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Laser Speckle Contrast Imaging in DIEP Breast Reconstruction: A Prospective Case Series Study

Abstract: Introduction: Laser speckle contrast imaging (LSCI) is a laser-based perfusion imaging technique that recently has been shown to predict ischemic necrosis in an experimental flap model and predicting healing time of scald burns. The aims were to investigate perfusion in relation to the selected perforator during deep inferior epigastric artery perforator (DIEP) flap surgery, and to evaluate LSCI in assisting of prediction of postoperative complications. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…LSCI, on the other hand, guarantees the recognition of blood vessels underneath the CAM as long as they are located close to the membrane and display a high perfusion status. This can be attributed to the fact that LSCI has to reach a penetration depth of approximately 300 µm when used for the measurement of dermal blood flow [ 61 , 62 , 63 ]. Therefore, the CAM assay application does not fully display the angiogenic development of deeper vessels and LSCI could be used as an additional tool here.…”
Section: Discussionmentioning
confidence: 99%
“…LSCI, on the other hand, guarantees the recognition of blood vessels underneath the CAM as long as they are located close to the membrane and display a high perfusion status. This can be attributed to the fact that LSCI has to reach a penetration depth of approximately 300 µm when used for the measurement of dermal blood flow [ 61 , 62 , 63 ]. Therefore, the CAM assay application does not fully display the angiogenic development of deeper vessels and LSCI could be used as an additional tool here.…”
Section: Discussionmentioning
confidence: 99%
“…Through the detection of erythrocyte flow at a tissue depth of 300 μm [ 56 ], superficial dermal perfusion could be noninvasively quantified through speckle pattern change detection. In contrast to ICGA, laser speckle contrast imaging (LSCI) allows wide-field imaging of 24 × 24 cm for continuous perfusion monitoring of a large flap without repetitive dye injection [ 57 ].…”
Section: Reviewmentioning
confidence: 99%
“…5 For a plastic surgeon, it is important to know which parts of the flap are viable for transplantation, and which parts may not. To et al 6 and Zötterman et al 7 showed that mounted LSCI can measure perfusion differences over the flap, but this has not been shown for a handheld LSCI device. Therefore, the research goal of this pilot study was to investigate whether the built handheld LSCI device could detect perfusion differences across the flap, and how perfusion varied during different stages of surgery.…”
Section: Introductionmentioning
confidence: 99%